Tiempo de espera para atención médica urgente en un hospital terciario después de implementar un programa de mejora de procesos - Taype-Huamaní, Waldo (2019)
Introduction. Overcrowding in emergency department of tertiary hospitals collapses its processes and prolongs waiting times. Objective. To evaluate waiting times for patients with urgent medical problems, in an emergency department after implementing a program of process improvement with facilitators. Methods. An observational study. Patients older than 14 years-old with priority III problems, who were attended between 6-23 hours, were included in the study. The team of facilitators was made up of trained administrative technicians (two each 8-hour period per day), who accelerated the diagnostic and therapeutic processes in outpatient. Waiting time for first attention and total length of stay in emergency services were measured. Results. 36 thousand attentions of priority III were evaluated, being higher in the fourth quarter of the year, on Monday, between 7 and 11 am. The median waiting time for arrival to provider was 35 minutes, and median time of length of stay in emergency was 2.9 hours. It were being longer when interconsultation is requested to another specialty (5 hours). 90% of attentions had a length stay in emergency less than five hours. Conclusion. The waiting time for emergency attention in priority III patients, after implementation of the process facilitator program, was similar to international standards.